BUMDes' CONTRIBUTION TO THE ACCELERATION OF MSME HALAL PRODUCT SUBMISSION: A STUDY IN TAMAN VILLAGE, PAITON DISTRICT - Musthafa Syukur (JURNAL HAKAM, 2025)
This study aims to analyze the contribution of Village-Owned Enterprises (BUMDes) in accelerating the halal certification application for MSMEs in Taman Village, Paiton District. Halal certification is crucial for MSMEs as it opens up wider market access, especially in modern retail and export markets. However, many MSME actors in Taman Village are still unaware of the halal certification process and face various administrative obstacles. This study employs an empirical legal research approach with interviews and field observations. The findings show that BUMDes plays a significant role as a facilitator by providing assistance, information, and acting as an intermediary between MSMEs and relevant agencies such as BPJPH. However, BUMDes' contribution in expediting the halal certification process is still limited by human resource capacity and a lack of inter-agency coordination. The study recommends enhancing BUMDes' internal capacity and collaborating with universities to strengthen their role in facilitating halal certification.